Pragmatics Analysis of Crosses in The Poetry of Ibrahim Ahmed Makri:An Analytical Study in the Light of The Theory of Verbal Acts (مجلة إحالات, 2026)
This research aims to analyze incidental verbal acts in the poetry of Ibrahim Ahmed Makri, according to the theory of verbal acts that highlight the role of language in achieving communicativegoals through context, intentionality, and achievement power. The research dealt with incidental verbs, such as declaration, reporting, and clarification, and deliberative tools that contributed to building poetic texts and enhancing their interaction with the recipient. The study focused on selected texts from Makri's poetry, showing that the poet employs the crosses with deep awareness tocommunicate spiritual meanings and moral values. The results confirmed that the incidental verbs inMakri's poetry contribute to achieving emotional and cognitive impact, taking advantage of thedeliberative context and poetic symbols to enrich the texts.